Migraciones y Familias InterAmericanas Testimonios: sufrimientos y esperanzas en tránsitos por México y desplazamientos en Chile - una perspectiva decolonial - Giebeler, Cornelia (Ensayos InterAmericanos, 2020)
The experience of writing with others facilitates a horizontal dialogue which allows us to get to know others and their migratory and family histories. From a decolonial perspective, the author presents testimonies of migration through Mexico and the displacements of Pewenche families as a result of hydroelectric installations in the South of Chile. This book contributes to making visible how family imaginaries are transformed by migration. The testimonies introduce an intimate view on the entanglements of personal experiences and the nuances of neoliberal-patriarchal societies in the Americas. The ideal of the "happy family", as well as the construction of the "poor migrant" lose their power because within the testimonies also appears the agency of the subject within the inter-American family and migratory changes.